2016
DOI: 10.1002/uog.15771
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of transvaginal ultrasound probes in a clinical setting: comparative performance of automated and manual reprocessing methods

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 28 publications
0
24
0
5
Order By: Relevance
“…Handle contamination decreased to background levels after disinfection with an automated system designed for simultaneous disinfection of the probe handle and body 16 . Others have reported similar figures (83% when the handle is not disinfected) 11 . The ultrasound transducer handle must therefore be considered a reservoir for microbial contaminants and a potential source of cross‐infection.…”
Section: The Need For Infection Prevention and Controlmentioning
confidence: 85%
See 1 more Smart Citation
“…Handle contamination decreased to background levels after disinfection with an automated system designed for simultaneous disinfection of the probe handle and body 16 . Others have reported similar figures (83% when the handle is not disinfected) 11 . The ultrasound transducer handle must therefore be considered a reservoir for microbial contaminants and a potential source of cross‐infection.…”
Section: The Need For Infection Prevention and Controlmentioning
confidence: 85%
“…The study found the probes were contaminated with bacteria and virus and the pooled prevalence of infected patients after a procedure was estimated to be 3.1% 10 . A German study reported that 21% of ultrasound probe bodies remained contaminated after disinfection with low‐level disinfectant wipes containing quaternary ammonium compounds 11 . There have also been reports of Doppler probes contaminated with skin flora, potentially pathogenic coliforms and diphtheroids as well as nosocomial staphylococci (coagulase negative and methicillin sensitive Staphylococcus aureus (MSSA)) 12 , 13 .…”
Section: The Need For Infection Prevention and Controlmentioning
confidence: 99%
“…Data are available that automated devices can reduce contamination of intracavity ultrasound probes to background levels [5]. One study showed that the automated device could reduce contamination with a success rate of 91.4% while a manual wipe method showed greater contamination (success rate of 78.8%) based on a study measuring bacterial contamination rates [12]. When asking sonographers about high-level disinfection with the automated device and glutaral-based soak systems, a higher level of satisfaction was reported for the automated system [22].…”
Section: Discussionmentioning
confidence: 99%
“…Disinfection methods presumably vary in many countries ranging from manual disinfection methods with impregnated wipes using quaternary ammonium compounds (QAC) to automated methods [12]. Recently, an automated sonicated hydrogen peroxide device (trophon ® EPR) has demonstrated its efficacy against native HPV16 and HPV18 virions [13].…”
Section: Introductionmentioning
confidence: 99%
“…FA ZIT: Für die Desinfektion von starren Endosonografiesonden kommen unterschiedliche Verfahren zur Anwendung: Behandlung mit viruziden Wischtüchern [117,118], Wischtücher plus Schaumanwendung [105], Tauchdesinfektionsverfahren [117,119], ein vollautomatisches Desinfektionssystem mit Wasserstoffperoxid-Aerosol [107,109,120,121] oder Verfahren, bei denen eine UV-C-Bestrahlung eingesetzt wird [122,123]. Während bei der alleinigen Anwendung von Wischtüchern zwar die meisten Bakterien, aber nicht immer auch alle Viren und keine bakteriellen Sporen abgetötet werden, werden mit den anderen Verfahren alle Mikroorganismen, z. T. inkl.…”
Section: Infektionen Nach Endovaginaler Sonografieunclassified